Cell-Free Fat Extract Improves Ovarian Function and Fertility in Mice With Advanced Age - Liu, Mengyu; Li, Wenzhu; Zhou, Xiaowei; Zhou, Mingjuan; Zhang, Wenjie; Liu, Qiang; Zhang, Aijun; Xu, Bufang (Frontiers in Endocrinology, 2022)
The reduction in the quantity and quality of oocytes is the major factor affecting fertility in women with advanced age, who tend to experience delayed childbearing and declined fertility rate. However, effective therapeutic strategies to combat this decrease in ovarian function are lacking in clinical practice. Thus, identifying a new method to rescue ovarian function and improve reproduction in natural age-related decline in fertility is necessary. Cell-free fat extract (CEFFE) has been verified to possess diverse active proteins exerting anti-aging and proliferation-promoting effects. Nonetheless, whether CEFFE can rescue the decline in aged-related ovarian function and improve the fertility of females with advanced age remains unclear. In this study, a natural aging mouse model, exhibiting similarities to the physiological changes of ovarian senescence, was used to observe the anti-aging effect of CEFFE on ovarian functions. We found that CEFFE, injected via the veins, could recover the levels of the sex hormone, increase angiogenesis and the number of growth follicles in the natural aging mice model. Moreover, CEFFE promoted the development of embryos and increased the litter size of aged mice. Transcriptome analysis of the aged mouse ovaries revealed that CEFFE treatment upregulated the expression of genes involved in the repair of DNA damage. And both in vivo and in vitro experiment proved that CEFFE improved the function of granulosa cells, including promoting proliferation, alleviating senescence, and rescuing DNA damage in aged granulosa cells. Collectively, our study implied that CEFFE improved the ovarian function and fertility of naturally aging mice by ameliorating the overall microenvironment of ovary, which provided a theoretical basis for new anti-aging therapeutic strategies for cell-free therapy in ovaries.